HES - Akkaya, Fatma Dogan (IGI Global, 2023)
The COVID-19 pandemic has led to the implementation of digital health surveillance systems worldwide, including Turkey's Hayat Eve Sığar (HES) platform. While effective in monitoring and tracing the virus, these systems also raise concerns about data privacy and cybersecurity risks. This chapter examines potential risks such as data breaches, malware attacks, unauthorized access, misuse of personal health information, and inadequate security protocols. To mitigate these risks, healthcare organizations must implement strong security measures and adopt a culture of security with a focus on continuous improvement and proactive risk management. The HES in Turkey provides a valuable case study for understanding these risks and measures to mitigate them. The chapter highlights the growing trend of digital health services invading individuals' private spaces and regulating their lives, emphasizing the importance of data privacy and security in safeguarding personal health information.
Keywords: 3. Good health